2017
DOI: 10.1111/ppl.12608
|View full text |Cite
|
Sign up to set email alerts
|

Inter‐ and intraspecific variability in physiological traits and post‐anoxia recovery of photosynthetic efficiency in grasses under oxygen deprivation

Abstract: Low oxygen conditions occur in grass sites due to high and frequent precipitation, poor soil quality, and over-irrigation followed by slow drainage. Three warm-season and one cool-season grass were analyzed at metabolic level during a time-course experiment performed in a controlled anoxic environment. Prolonged oxygen depletion proved detrimental by leading to premature death to all the species, with the exception of seashore paspalum. Moreover, the anoxia tolerance observed in these grasses has been associat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 44 publications
1
12
0
Order By: Relevance
“…Wils., or Gaeumannomyces graminis var. graminis , which can develop perfectly under these environmental conditions (Pompeiano et al., 2017a).…”
Section: Introductionmentioning
confidence: 99%
“…Wils., or Gaeumannomyces graminis var. graminis , which can develop perfectly under these environmental conditions (Pompeiano et al., 2017a).…”
Section: Introductionmentioning
confidence: 99%
“…previously reported that among eight seashore paspalum genotypes there were differences in tolerance to anoxia (Pompeiano et al, 2017). Tan et al (2010) reported that bermudagrass can endure long-term and deep submergence.…”
Section: Methodsmentioning
confidence: 98%
“…Reduction in root respiration rates have been observed in many plants under anoxia, regardless of whether the plants are flooding tolerant or intolerant (Carpenter and Mitchell, 1980;Kuo and Chen, 1980;Lambers, 1976;Liao and Lin, 1995;Lin and Lin, 1992;Su and Su, 1996). Pompeiano et al (2017) found that improved tolerance to anoxia in seashore paspalum may be due to reduced respiration but not necessarily sugar starvation. Given the increased reliance on anaerobic metabolism for energy during waterlogging, changes in fermentation usually represent adaptive strategies for waterlogging tolerance (Xu et al, 2014).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Total soluble sugars quantification. Total soluble sugars (TSS; sucrose, glucose and fructose) from epigeal, hypocotyl and root organs were extracted and assayed as previously reported 17 . The accuracy of the method was calibrated using standards with known amounts of carbohydrates.…”
Section: Biometric Analysismentioning
confidence: 99%